Radical formation in cytochrome c oxidase() - Yu, Michelle A. (Biochim Biophys Acta, 2011)
The formation of radicals in bovine cytochrome c oxidase (bCcO), during the O(2) redox chemistry and proton translocation, is an unresolved controversial issue. To determine if radicals are formed in the catalytic reaction of bCcO under single turnover conditions, the reaction of O(2) with the enzyme, reduced by either ascorbate or dithionite, was initiated in a custom-built rapid freeze quenching (RFQ) device and the products were trapped at 77 K at reaction times ranging from 50 µs to 6 ms. Additional samples were hand mixed to attain multiple turnover conditions and quenched with a reaction time of minutes. X-band (9 GHz) continuous wave electron paramagnetic resonance (CW-EPR) spectra of the reaction products revealed the formation of a narrow radical with both reductants. D-band (130 GHz) pulsed EPR spectra allowed for the determination of the g-tensor principal values and revealed that when ascorbate was used as the reductant the dominant radical species was localized on the ascorbyl moiety, and when dithionite was used as the reductant the radical was the SO(2)•(−) ion. When the contributions from the reductants are subtracted from the spectra, no evidence for a protein-based radical could be found in the reaction of O(2) with reduced bCcO. As a surrogate for radicals formed on reaction intermediates, the reaction of hydrogen peroxide (H(2)O(2)) with oxidized bCcO was studied at pH 6 and pH 8 by trapping the products at 50 µs with the RFQ device to determine the initial reaction events. For comparison, radicals formed after several minutes of incubation were also examined, and X-band and D-band analysis led to the identification of radicals on Tyr-244 and Tyr-129. In the RFQ measurements, a peroxyl (R – O – O•) species was formed, presumably by the reaction between O(2) and an amino acid-based radical. It is postulated that Tyr-129 may play a central role as a proton loading site during proton translocation by ejecting a proton upon formation of the radical species and then becoming reprotonated during its reduction via a chain of three water molecules originating from the region of the propionate groups of heme a(3).